A Simple, Inexpensive, and Portable Image-Based Technique for Nondestructive Leaf Area Measurements - Shinsuke Agehara; Lillian Pride; Mariel Gallardo; Jose Hernandez-Monterroza (EDIS)
This new 6-page article, part of a series introducing various image-based measurements for horticultural research, introduces a simple, inexpensive, and portable image-based technique for nondestructive leaf area measurements. It uses an imaging apparatus made with ordinary office supplies to obtain leaf images in greenhouse or field environments. Leaf images are then processed and analyzed to measure leaf area using ImageJ, an open-source image processing program. Because both image capture and analysis are performed nondestructively, leaf area can be measured on the same leaf repeatedly, enabling the monitoring of leaf growth over time, as well as photosynthesis and transpiration. This technique is particularly useful to researchers and students studying leaf growth and physiology in greenhouse or field environments. Written by Shinsuke Agehara, Lillian Pride, Mariel Gallardo, and Jose Hernandez-Monterroza, and published by the UF/IFAS Horticultural Sciences Department. https://edis.ifas.ufl.edu/hs1395